Immune checkpoint inhibitor toxicity: A new indication for therapeutic plasma exchange?. Issue 4 (1st March 2021) - Compton, Frances; He, Lin; Sarode, Ravi; Wodajo, Amelework; Usmani, Amena; Burner, James; Berlacher, Mark; De Simone, Nicole
Abstract: Novel immune‐modulating anticancer drugs are being used with increasing frequency. With increased use, there are more frequent cases of toxicities caused by these drugs, termed immune‐related adverse events (irAEs). We present a case in which we successfully treated a case of severe, steroid‐refractory, nivolumab‐induced myocarditis with therapeutic plasma exchange (TPE). Nivolumab is an immune checkpoint inhibitor (ICI) which blocks programmed death receptor‐1 (PD‐1). This blockade allows for enhanced T‐cell function and increased anti‐tumor response. The patient presented with signs and symptoms of heart failure and was found to have a significantly depressed cardiac ejection fraction. Over the course of her five TPE procedures, she improved clinically and was discharged home with improved left ventricular ejection function. This case suggests an emerging role of TPE in the management of severe ICI‐induced toxicity, such as myocarditis.